Association of religious coping use with psychological well-being of mother of mentally retarded children - Sak Liung; Carla Raymondalexas Marchira; Irwan Supriyanto; Mahar Agusno; Soewadi Soewadi; Sumarni Sumarni (Journal of Community Empowerment for Health, 2019)
Low psychological well-being in mothers of children with mental retardation can affect maternal mental health and quality of life. Psychological well-being of mothers depend on maternal coping strategies to overcome the burden of childcare. The religious background of Indonesian society makes mothers tend to use religious coping in handling the burden of nurturing their children. Aim of this study to determine the association between religious coping use and psychological well-being of mothers of children with mental retardation. This is an analytic descriptive study with cross-sectional design. Subjects were mothers of children with mild to moderate level of mental retardation, students of SLB Negeri 1 Bantul. The psychological well-being and religious coping of mother is assessed by Indonesian version of the Psychological Well-being Scale and Religious Coping Scale. The significance level of the statistical test is expressed at p < 0.05. Results of this study showed there is a significant association between religious coping and psychological well-being of mothers of children with mental retardation (X2: 17.897; C: 0.377; p: 0.000; RP: 5.65; 95% CI: 2.46-12.92). All dimensions of religious coping have a significant association with the psychological well-being of the mother (p: 0.000). The dimensions of achieving comfort and closeness to God have the highest closeness association with the psychological well-being among other dimensions of religious coping (X2: 39.041; C: 0.515). The confounding variables in this study are mother’s age, mother’s education, family income, marital status, mother’s employment status, family income, children’s gender, children's level of mental retardation and children’s class grade. Mother’s education has also a significant association with the psychological well-being of the mother (p: 0.021). Religious coping and mother’s education contribute 26.7% to the psychological well-being of mothers. This finding reveals that religious coping is important to improve the psychological well-being of mothers of children with mental retardation.